The Prabhakaran saga : the rise and fall of an Eelam warrior - Murari, S. (Sage Publications India Pvt. Ltd., 2012)
This is the story of the man who defined the armed struggle for an independent Eelam for over three decades and who lived by the gun and died by the gun-Velupillai Prabhakaran. A home-grown guerilla who built the LTTE into a ruthless war machine and controlled its world-wide network from his hideout and ruled territories under his control with an iron fist; who defied the world and eliminated whoever came in his way, including former Indian Prime Minister Rajiv Gandhi; who had fighters ready to kill and die in thousands for him ... yet he failed, leaving the future of Sri Lankan Tamils a big que.